The Role of Supply Chain Resilience and Integration in Enhancing the Supply Chain Performance: A Literature Review - Khan, Tahsina; Habib, Md. Mamun (International Journal of Supply Chain Management, 2025)
This research aims to investigate the impact of supply chain resilience and integration on the performance of FMCG firms in Bangladesh. The primary objective is to synthesize existing literature to comprehend how these two interdependent capabilities enhance operational efficiency, delivery reliability, flexibility, innovation, and customer satisfaction in a developing economy. This research used a narrative and integrative review methodology, examining peer-reviewed journal articles, conference proceedings, and industry reports mostly published in the last decade. The technique included the thematic classification of literature into resilience, integration, and performance dimensions, followed by an iterative process of synthesis and interpretation. The study highlights findings that supply chain resilience, which includes adaptation, flexibility, visibility, redundancy, and recovery capacity, allows organizations to successfully absorb and recover from disturbances. The outcomes of the study emphasize the significant role of Supply chain integration to facilitate coordination, information exchange, and cooperation, hence enhancing resilience. Therefore, the research offers actionable insights for managers in cultivating robust and cohesive supply chains, governments in fostering enabling infrastructure and technology integration, and industry stakeholders in advancing collaborative networks.